Worldwide trends in cervical cancer incidence and mortality, with predictions for the next 15 years. Issue 21 (9th August 2021) - Lin, Shujuan; Gao, Kai; Gu, Simeng; You, Liuqing; Qian, Sangni; Tang, Mengling; Wang, Jianbing; Chen, Kun; Jin, Mingjuan
Abstract : Background: Cervical cancer is 1 of the most common cancers in females worldwide. Understanding the most recent global patterns and temporal trends of cervical cancer burden might be helpful for its prevention and control. Methods: Data on cervical cancer (International Classification of Diseases, Tenth Revision, code C53) incidence and mortality in 2018 were extracted from the GLOBOCAN 2018 database and further analyzed for their correlations with the Human Development Index. Temporal trends were analyzed using the annual percent change with joinpoint analysis among 31 countries with highly qualified data from the Cancer Incidence in Five Continents Plus and World Health Organization mortality databases. Future trends for the next 15 years were predicted using an open‐source age‐period‐cohort model. Results: Cervical cancer incidence and mortality rates were both negatively correlated with the Human Development Index ( r = −0.56 for incidence, r = −0.69 for mortality; P < .001) in cross‐sectional analysis, and both remained stable in 12 countries or even decreased in 14 and 18 countries for incidence and mortality, respectively, during the most recent 10 data years. Similar findings were observed for the next 15 years. Conclusions: Cervical cancer burden was correlated with socioeconomic development. An overwhelming majority of countries had stable or decreasing trends in incidence and mortality rates, especially in those with effective cervical cancer screening programs and human papillomavirus vaccination. Lay Summary: The authors investigated the most up‐to‐date data from official databases released by the International Agency for Research on Cancer and found that cervical cancer incidence and mortality were negatively correlated with socioeconomic development. Among the 31 countries analyzed, most (26 countries were analyzed for incidence, and 30 were analyzed for mortality) had stable or even decreasing temporal trends over the most recent 10 years, especially in those with effective cervical cancer screening programs. In addition, the predicted trends for the next 15 years were basically consistent with the observed trends among most of the analyzed countries (19 countries for incidence and 26 countries for mortality). Abstract : Globally, cervical cancer incidence and mortality rates are negatively correlated with socioeconomic development. Both the temporal and predicted trends of incidence and mortality rates remain stable or even decrease in most of the analyzed populations, especially in those with effective cervical cancer screening programs and human papillomavirus vaccination.